GAME EDUKASI TEBAK BANGUN RUANG DAN BANGUN DATAR UNTUK KELAS 1 MENGGUNAKAN CONSTRUCT 2 BERBASIS HTML5 - Priyambodho, Dimas Dwi Cahyo; Kanedi, Indra; Lianda, Deri (Jurnal Ilmiah Rekayasa dan Manajemen Sistem Informasi, 2023)
Technology development is running very fast along with human needs. The rapid development of technology also extends to the world of education. One of the technological developments is educational games which were created as learning media to support teacher teaching and learning activities. This study aims to build a game as a means of increasing students' knowledge of the types and shapes of plane shapes and geometric shapes. This Educational Game was built using the Multimedia Development Life Cycle (MDLC) method with the game development stages consisting of concept, design, material collecting, assembly, testing and distribution. The results that can be obtained in this study are to create a game application as a learning media for class 1 of Elementary School in the introduction of  the two and three-dimensional figure for class 1 using  HTML5-based.